The Effects of Applying Communitary Policy Upon the Romanian Energetic System and the Future Directions Regarding Sustainable Development - Larisa Luchian; Raluca Gabriela Dulgheriu (CES Working Papers, 2014)
The study provides an overview on the effects and perspectives of implementation of sustainable development policies in the energy sector in Romania, by reference to the European Union. The purpose of this study is to highlight, by interpretation of the analyzed indicators, how becoming a member of the European Union has helped to improve living standards by assuming the defined objective of sustainable consumption and production. Thus, the pre and post accession trends of electricity consumption, the dependence on imported energy, the negative impact of the use of traditional energy sources on the environment and the importance of the EU Directives on finding alternative sources to support the production and energy consumption were analysed.
Keywords: Q2; Q3; Q4; P28; 330; socioeconomic development; sustainable consumption and production; energy dependence; renewable energy Romania